Pengaruh Penggunaan Media Sangrai Pasir Putih dan Pasir Hitam Terhadap Karakteristik Rendemen dan Bilangan Asam Minyak Kemiri Dari Daerah Asal NTT. - Silvana Kholid Bahadi; Aldi Budi Riyanta; Purgiyanti Purgiyanti (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
Candlenut (Aleurites Moluccana (L.) Willd) is a plant commodity that has the potential to be developed. Candlenut processing also varies, one of which is that candlenut oil can be made and then its benefits can be taken. In making the candlenut oil, it uses the oil press method with a press machine that has previously been roasted using black sand or white sand media. The characteristics of the candlenut oil include yield and acid number. The yield of hazelnut oil on black sand is 47.55% and on white sand is 46.80%. And the results of the acid number on black sand are 1.8% while on white sand is 2.1%. Based on these results, it can be concluded that the use of black sand and white sand as a roasting medium affects the yield characteristics and acid number of candlenut oil.